Multilateral development banks: contributions and challenges - Abor, Joshua Yindenaba; Subramanian, Lakshmy; Iddrisu, Khadijah; Nsor-Ambala, Randolph (Springer, 2024)
This chapter examines the contributions of Multilateral Development Banks (MDBs) as well as discusses the challenges confronting them. MDBs obtain their funding from a variety of sources, including the global capital market, contributions and special donations from members, proceeds from the issue of bonds and partnerships, etc., which aid in their ability to fund their activities. Their main operations include the provision of financing, the creation of knowledge products, and serving as a significant source of data collection and analysis, which results in the improvement of policy and the generation of ideas for efficient policy planning and execution. Their contributions include providing a steady source of funding, aiding middle-income nations, meeting a range of development needs, and providing a variety of complementary comparative advantages. However, the severity and regularity of numerous crises have also created major difficulties for MDBs, including resource competition, increase in ad hoc funding decisions, funding vulnerabilities, proliferation of MDB alternatives, and geographical distribution of power. In order to align national and global requirements, it is crucial to revamp the financing patterns of multilateral activities. This can be achieved through the implementation of innovative financial and policy incentives, meticulous evaluation of multilateral funding decisions, enhanced data collection mechanisms, and a more effective prioritisation of multilateral activities.